Kinetics and mechanism of the biodegradation of PLA/clay nanocomposites during thermophilic phase of composting process. (August 2015) - Stloukal, Petr; Pekařová, Silvie; Kalendova, Alena; Mattausch, Hannelore; Laske, Stephan; Holzer, Clemens; Chitu, Livia; Bodner, Sabine; Maier, Guenther; Slouf, Miroslav; Koutny, Marek
Graphical abstract: Highlights: Composting is a useful technique for disposal of PLA nanocomposite materials. The addition of nanoclays shortened the lag phase of biodegradation process. The abiotic hydrolysis was identified as the rate-limiting step of biodegradation. PLA chains must be shortened beyond a certain MW to be mineralized. An effective tool is provided for predicting the time of composting. Abstract: The degradation mechanism and kinetics of polylactic acid (PLA) nanocomposite films, containing various commercially available native or organo-modified montmorillonites (MMT) prepared by melt blending, were studied under composting conditions in thermophilic phase of process and during abiotic hydrolysis and compared to the pure polymer. Described first order kinetic models were applied on the data from individual experiments by using non-linear regression procedures to calculate parameters characterizing aerobic composting and abiotic hydrolysis, such as carbon mineralization, hydrolysis rate constants and the length of lag phase. The study showed that the addition of nanoclay enhanced the biodegradation of PLA nanocomposites under composting conditions, when compared with pure PLA, particularly by shortening the lag phase at the beginning of the process. Whereas the lag phase of pure PLA was observed within 27 days, the onset of CO2 evolution for PLA with native MMT was detected after just 20 days, and from 13 to 16 days for PLA with organo-modified MMT. Similarly, the hydrolysis rate constants determined tended to be higher for PLA with organo-modified MMT, particularly for the sample PLA-10A with fastest degradation, in comparison with pure PLA. The acceleration of chain scission in PLA with nanoclays was confirmed by determining the resultant rate constants for the hydrolytical chain scission. The critical molecular weight for the hydrolysis of PLA was observed to be higher than the critical molecular weight for onset of PLA mineralization, suggesting that PLA chains must be further shortened so as to be assimilated by microorganisms. In conclusion, MMT fillers do not represent an obstacle to acceptance of the investigated materials in composting facilities.